A Practical Review of the Management of Xanthelasma palpebrarum - Hamid Malekzadeh, MD; Benjamin Ormseth, BS; Jeffrey E. Janis, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Xanthelasma palpebrarum is the most common type of xanthomatous lesion. Various methods for treating Xanthelasma palpebrarum have been reported. We conducted a systematic review to evaluate the efficacy and associated complications of different treatment methods, and we summarized these findings as a practical review designed to be clinically useful, accessible, and impactful. Methods:. The PubMed and Embase databases were searched to identify clinical studies that reported on outcomes and complications of different methods of Xanthelasma treatment. The electronic databases were searched from January 1990 to October 2022. Data on study characteristics, lesion clearance, complications, and recurrences were collected. Results:. Forty-nine articles (including 1329 patients) were reviewed. The studies reported on surgical excision, laser modalities, electrosurgical techniques, chemical peeling, cryotherapy, and intralesional injection. The majority of studies were retrospective (69%) and single-arm (84%). Surgical excision combined with blepharoplasty and skin grafts showed excellent outcomes for large Xanthelasma. CO2 and erbium yttrium aluminum garnet (Er:YAG) were the most commonly studied lasers and showed more than 75% improvement in over 90% and 80% of patients, respectively. Comparative studies reported better efficacy for CO2 laser than both Er:YAG laser and 30%–50% trichloroacetic acid. Dyspigmentation was the most encountered complication. Conclusions:. Different methods for the treatment of Xanthelasma palpebrarum have been reported in the literature, with moderate to excellent efficacy and safety profiles depending on the size and location of the lesion. Surgery is more appropriate for larger and deeper lesions, whereas laser and electrosurgical techniques can be used in smaller and more superficial contexts. Only a limited number of comparative studies have been conducted, and novel clinical trials are necessary to further augment appropriate treatment selection.